Generation of leukotrienes by human monocytes upon stimulation of their beta-glucan receptor during phagocytosis. - Czop, J K (1985)
Human monocytes possess a receptor for ingestion of particulate activators of the human alternative complement pathway that functions in the absence of plasma proteins and is distinct from the receptors for Fc-IgG and the major cleavage fragment of the third component of complement (C3b). Incubation of monolayers of monocytes with 1.1 X 10(6) to 2.2 X 10(7) glucan particles per ml initiated a phagocytic response comparable to that obtained with zymosan particles, of which beta-glucan is a constituent along with mannan. Maximal quantities of 4.93 +/- 3.43 ng of leukotriene B4 (LTB4) and 0.43 +/- 0.23 ng of leukotriene C4 (LTC4) (mean +/- SD, n = 3) were released by 10(6) monocytes stimulated with 1.1 X 10(7) glucan particles per ml. Preincubation of monocytes with 50 micrograms of soluble beta-glucan per ml reduced subsequent monocyte ingestion of 5 X 10(6) zymosan particles per ml and 2.2 X 10(6) glucan particles per ml by 52% and 55%, respectively, and diminished release of LTB4 by monocytes stimulated with 2 X 10(8) zymosan particles per ml and 8.6 X 10(6) glucan particles per ml by 73% and 61%, respectively. Preincubation with 1 mg of soluble mannan per ml had little effect on monocyte phagocytosis or LTB4 generation in response to either zymosan or glucan particles, and neither soluble beta-glucan nor mannan stimulated generation of LTB4 or LTC4. The effect of pretreatment of monocytes with soluble beta-glucan was time dependent, with the maximal effect being evident within 20 min of pretreatment, and was specific for zymosan or glucan particles in that the LTB4 and LTC4 release induced by 2.5 microM calcium ionophore A23187 was unaffected. That both phagocytosis and leukotriene generation are inhibited by soluble beta-glucan but not by mannan at a rate compatible with the phagocytic process of monocyte monolayers indicates ligand specificity for a beta-glucan receptor. As the beta-glucan receptor recognizes particulate activators of the alternative complement pathway, the nonimmune response to a single stimulus induces complement activation, phagocytosis, and leukotriene generation.